PENINGKATAN AKTIVITAS DAN HASIL BELAJAR APRESIASI SENI RUPA DENGAN METODE COOPERATIVE LEARNING TIPE STAD SISWA KELAS VIII.1 SMP NEGERI 6 PARIAMAN - AIN NURROHMAH, Wisdiarman, Zubaidah (Universitas Negeri Padang, 2013)
The purpose of this research is 1) to improve students activity in learning through cooperative learning STAD in art lesson at SMP N 6 Pariaman, 2) to improve the the result of learning in art lesson through the using of cooperative learning STAD type at SMP N 6 Pariaman. Type of this research is classroom action research. Subject of this research is students of VIII 1 SMP N 6 Pariaman. Total of students are 19 students. This research is hel in VIII 1 SMP N 6 Pariaman, Jln Gondoriah No 70 K, Pariaman, West Sumatera. This research is held of two cycle, technique of collecting data through observation form, result observation. Technique of analysis data use percentage formula. The result of this research conclude that the using of cooperative learning STAD can improve students activity in learning art lesson. This method also can improve the achievement of students in learning art lesson, VIII 1 class at SMP N 6 Pariman. At the pre- cycle, the mean of students ability is 62,47 then at the first cycle 68,89 and rised at the second cycle, 86,84.